Narrativités 2.0 : fragmentation-organisation d’un métadiscours - Céline Masoni Lacroix (Cahiers de Narratologie)
Fans’ analysis of their creative practices and of writing generally, academics’ capture of this narrative and discursive material represent a heterogeneous collection of meta-discourses. How is this circulation of « meta » narratives and discourses expressing a reflexive thinking about writing? We focus on a discursive spread as a fragmentation-organization process, which does not bring into conflict fans and academics’ metanarratives and metadiscourses, but apprehends a binding dichotomy or a co-extensive principle (Masoni Lacroix & Cailler, 2016), which expose this multiplicity. We stress on an emancipating-(re)normalizing movement of writing, named met@ttachment, as a constitutive principle of fannish narrativities, having an effect on scientific writing.